2019
DOI: 10.1002/ppul.24314
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity among children with asthma: Cross‐sectional analysis in the UK millennium cohort

Abstract: Background Although beneficial for health and well‐being, most children do not achieve recommended levels of physical activity. Evidence for children with asthma is mixed, with symptom severity rarely considered. This paper aimed to address this gap. Methods We analyzed cross‐sectional associations between physical activity and parent‐reported asthma symptoms and severity for 6497 UK Millennium Cohort Study 7−year‐old participants (3321, [49%] girls). Primary outcomes were daily moderate‐to‐vigorous physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 35 publications
8
40
0
Order By: Relevance
“…However, in this present research, objective asthma specific markers of severity such as lung function and markers of Type 2 high disease did not correlate with perceived barriers to exercise. Similarly, a cross-sectional analysis of physical activity in the UK millennium cohort demonstrated that activity levels in children with asthma were not affected by the severity of their disease [36]. This is a clinically relevant finding which suggests that severity of disease is not necessarily a barrier to exercise.…”
Section: Perceived Symptom Burden Impacts Perceived Barriers To Exercisementioning
confidence: 91%
See 1 more Smart Citation
“…However, in this present research, objective asthma specific markers of severity such as lung function and markers of Type 2 high disease did not correlate with perceived barriers to exercise. Similarly, a cross-sectional analysis of physical activity in the UK millennium cohort demonstrated that activity levels in children with asthma were not affected by the severity of their disease [36]. This is a clinically relevant finding which suggests that severity of disease is not necessarily a barrier to exercise.…”
Section: Perceived Symptom Burden Impacts Perceived Barriers To Exercisementioning
confidence: 91%
“…This appears to be a key stage for engagement in sport in later life, with a report from The Women in Sport Research group showing that if children start to drop out of sporting activities at this age then they tend not to reengage as adults [35]. Comparatively, exercise levels in children at age 7 are not reduced in those with a diagnosis of asthma [36]. It may be that diagnosis at this age compounds the effects of this transition point.…”
Section: Differentially Perceived Barriers To Exercise Dependent On Amentioning
confidence: 99%
“…Previous studies have relied upon self‐reported data on physical activity and only a few smaller studies measured physical activity objectively. We read with great interest the study by Pike et al 1 that focuses on the association between parent‐reported asthma diagnosis and physical activity measured by the accelerometer in 6497 children aged 7 years from the UK Millennium Cohort Study. Only half of the children met the recommendation of at least 60 minutes of MVPA per day.…”
mentioning
confidence: 99%
“…The study by Pike et al 1 adds valuable and good‐quality evidence on the association between asthma and physical activity in children, but the authors did not provide information on asthma symptoms triggered by exercise or results of exercise challenge testing. We believe this information would be important when studying the association between asthma and physical inactivity in children.…”
mentioning
confidence: 99%
See 1 more Smart Citation